Survey on risk management practices and Basel II implementation : emphasis on capital adequacy, market and operational risks - Eng, Yi Yuan (2008)
With more than 100 countries worldwide expected to implement Basel II in 2007-2009, there is currently an immense interest in the readiness of banks in meeting the implementation deadline. Consequently, our final year research project seeks to determine the extent to which banks are disclosing information in accordance with Basel II Pillar 3 requirements and industry risk management practices that are imperative to users of financial statements albeit discretionary under Pillar 3. Using our conceptualized disclosure index, we survey the disclosure quality of 1140 annual reports from 300 banks across the globe for years 2000 to 2004 (where available) and analyze the characteristics of banks that possess stronger risk management disclosure. We further examine the degree of adherence to Pillar 1 minimum capital adequacy ratio (CAR) and assess the implications of Pillar 2 national supervisors’ discretion in implementation by reviewing the regulatory publications of banking authorities in 22 countries. Our time series analysis shows that risk management disclosure and adoption of best industry practices have improved significantly over the years.